Qian nü you hun Chinese ghost story / Cinema City Company Limited ; screenplay, Yuen Kai Chi ; produced by Tsui Hark ; director, Ching Siu Tung. - Pu, Songling, 1640-1715 (G-Juxing, 2004)
"Ning Tsai-Shen, a humble tax collector, arrives in a small town to carry out his work. Unsurprisingly, no-one is willing to give him shelter for the night, so he ends up spending the night in the haunted Lan Ro temple. There, he meets Taoist Swordsman Yen Che-Hsia, who warns him to stay out of trouble, and the beautiful Nieh Hsiao-Tsing, with whom he falls in love. Unfortunately, Hsiao-Tsing is a ghost, bound for all eternity by a hideous tree spirit with an incredibly long tongue that wraps itself round its victims and sucks out their life essence (or 'yang element')"--IMDb.com.